2018
DOI: 10.1016/j.stemcr.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

An mTOR Signaling Modulator Suppressed Heterotopic Ossification of Fibrodysplasia Ossificans Progressiva

Abstract: SummaryFibrodysplasia ossificans progressiva (FOP) is a rare and intractable disorder characterized by extraskeletal bone formation through endochondral ossification. FOP patients harbor gain-of-function mutations in ACVR1 (FOP-ACVR1), a type I receptor for bone morphogenetic proteins. Despite numerous studies, no drugs have been approved for FOP. Here, we developed a high-throughput screening (HTS) system focused on the constitutive activation of FOP-ACVR1 by utilizing a chondrogenic ATDC5 cell line that stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 67 publications
1
49
0
Order By: Relevance
“…Two of them, a human specific antiactivin antibody (REGN2477, Regeneron, NCT03188666; Regeneron Pharmaceuticals, Tarrytown, NY, USA) and a RARγ agonist (Palovarotene, NCT02279095; Clementia, Montreal, Canada) are currently in clinical trials. In addition, the mTOR inhibitor rapamycin (Sirolimus(42); Rapamune, Pfizer, New York, NY, USA), the repurposed Src inhibitor anticancer drug saracatinib (AstraZeneca Pharmaceuticals, Cambridge, UK) that also inhibits ALK2 signaling, an anti‐ALK2 blocking antibody by Daiichi Sankyo (Tokyo, Japan) and Saitama University (Saitama, Japan), and three ALK2 kinase inhibitors (Blueprint Medicines, Cambridge, MA, USA; La Jolla Pharmaceutical Co, San Diego, CA, USA; BioCryst Pharmaceuticals, Durham, NC, USA) have been publicly reported. Apart from waiting for the outcome of clinical trials where periodic systemic administration is considered, it would be of interest to explore whether these drugs may be useful applied locally, eg, surgery to remove heterotopic bone, or for example, in combinations at a lower dose.…”
Section: Discussionmentioning
confidence: 99%
“…Two of them, a human specific antiactivin antibody (REGN2477, Regeneron, NCT03188666; Regeneron Pharmaceuticals, Tarrytown, NY, USA) and a RARγ agonist (Palovarotene, NCT02279095; Clementia, Montreal, Canada) are currently in clinical trials. In addition, the mTOR inhibitor rapamycin (Sirolimus(42); Rapamune, Pfizer, New York, NY, USA), the repurposed Src inhibitor anticancer drug saracatinib (AstraZeneca Pharmaceuticals, Cambridge, UK) that also inhibits ALK2 signaling, an anti‐ALK2 blocking antibody by Daiichi Sankyo (Tokyo, Japan) and Saitama University (Saitama, Japan), and three ALK2 kinase inhibitors (Blueprint Medicines, Cambridge, MA, USA; La Jolla Pharmaceutical Co, San Diego, CA, USA; BioCryst Pharmaceuticals, Durham, NC, USA) have been publicly reported. Apart from waiting for the outcome of clinical trials where periodic systemic administration is considered, it would be of interest to explore whether these drugs may be useful applied locally, eg, surgery to remove heterotopic bone, or for example, in combinations at a lower dose.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other molecules, such as TGF-β neutralizing antibody (Wang et al, 2018) and transferrin receptor 2 (Rauner et al, 2019), and some drugs, such as insulin (Zhang et al, 2014) and desloratadine (Kusano et al, 2020), could attenuate heterotopic ossification formation induced by BMPs. A previous study also showed that mTOR signaling modulator suppressed heterotopic ossification formation (Hino et al, 2018); metformin exerted a dual negative regulatory effect on mTOR and BMP signal, and it might inhibit heterotopic ossification through an mTOR-BMP crosstalk signaling network (Wu et al, 2019). Recently, synthetic retinoid agonists, as a new option, has shown promise because it inhibited BMP-mediated heterotopic ossification formation in animal models (Sinha et al, 2016), and retinoid agonist therapy is being examined in patients with a rare, genetic form of heterotopic ossification (Lowery and Rosen, 2018).…”
Section: Discussionmentioning
confidence: 90%
“…Hopefully, an effective treatment will be available to halt the formation of HO in the near future. To date, four potential drugs are tested in a clinical trial: Palovarotene, Garatosmab, Rapamycin and Saracatinib (32)(33)(34)(35). Once found effective in preventing HO formation, surgical treatment might be an option to unlock joints or to safely operate an FOP patient for any other condition under an umbrella of one (or a combination) of these drugs.…”
Section: Discussionmentioning
confidence: 99%